Revisitando o movimento estudantil de 1968: a trajetória dos estudantes do interior paulista - Augustinho, Aline Michele Nascimento (Universidade Federal de São Carlos, 2010)
The year 2008 was full of "celebration" about the mythical 1968. Universities, newspapers and television networks devoted their attention to the forty-year cycle of major political demonstrations student of brazilian history. Besides remembering the student uprising, we must think what is left of this movement to contemporary politics, as these actors observe and reinterpret their past attitudes. It is clear that the ideals of the former student left is no longer the same. Many of the former militants, who have achieved political power, have their practices related to manifestations of forty years ago. One hypothesis that guides this dissertation is that the time changes the structures and the social and the ways of political scenario depend on a constantly rewritten history. Since the two main political student from 1968 to guarantee excellence of the university and public repudiation of the military regime, it is interesting how these same people act as they are now members of the political elite. Using the methodology of work the tools of 'Oral History' and 'Paths of Life', this research addresses the student struggles of the period, through the oral histories of some of the student leaders of 1968. Throughout the process of democratization, the dominant structures able to absorb important part of proposals for new groups of social movements that have emerged since the 1970s, as the movements of women, homosexuals and ethnic minorities, and also the proposals related to the revolution behavior and culture of the 1960s. In this scenario, the former student activists of the left had to readjust their goals, platforms and agendas as they entered politics through the new parties that formed in the late 1970s. The uniqueness of man is also a way of revealing how people universalized through their lives and their actions, the historical era in which they live, thus revealing hidden pathways still a movement that was also trainer of the contemporary political scene.
Keywords: Ciência política; Ditadura militar; Movimentos sociais; Participação política; Movimento estudantil; Regime militar; Student movement; Social movements; Military regime; CIENCIAS HUMANAS::CIENCIA POLITICA